OP0213 Systemic Sclerosis is Associated with a Unique Colonic Microbial Consortium. (9th June 2015) - Volkmann, E.; Chang, Y.-L.; Barroso, N.; Furst, D.; Clements, P.; Tong, M.; Roth, B.; Conklin, J.; Getzug, T.; Braun, J.
Abstract : Background: Gastrointestinal tract (GIT) dysfunction affects most patients with systemic sclerosis (SSc) and is a leading cause of morbidity. While the etiology of SSc-related lower GIT dysfunction remains elusive, evidence suggests that bacterial overgrowth is a feature of SSc. However, no studies have directly examined the colonic microbial consortium of SSc patients. Objectives: To compare colonic microbial composition of SSc patients and healthy controls. To determine whether microbial composition alterations are associated with lower GIT symptoms. Methods: Adults SSc patients who had no contraindication to colonoscopy were eligible to participate. Patients were excluded if they were on chronic antibiotic therapy. Healthy controls were age- and gender-matched to SSc patients (1:1). At baseline, participants underwent a colonoscopy and cecum and sigmoid mucosal lavage samples were obtained. Patients also completed the GIT 2.0 questionnaire to assess GIT symptom severity at the time of colonoscopy. The microbiota from these samples were determined by Illumina HiSeq 2000 16S sequencing, and operational taxonomic units (OTU) were selected using the Greengenes database at 97% identity. Similarity between microbial communities in sample groups were determined by computing unweighted UniFrac distances between samples with QIIME. Principal coordinate analysis (PCoA) was performed to visualize the resulting UniFrac distance matrix. To identify differentially abundant bacterial phylotypes at the genus-taxonomy level, pairwise comparisons (Kruskal-Wallis test) between SSc and healthy samples were computed. Multiple hypothesis tests were adjusted by computing Benjamini and Hochberg false discovery rates (FDR) and a significant association was defined at the FDR q-value threshold below 0.05. Results: 17 patients with SSc (88% Female; Median age 52.1 years; Median disease duration 7.1 years) underwent colonoscopy. The mean (SD) GIT 2.0 scores were: Total: 0.7 (0.6); Distension/Bloating: 1.5 (0.9); Fecal soilage 0.5 (0.9); Diarrhea 0.4 (0.6); Social functioning 0.5 (0.5); Emotional Well-being 0.5 (0.7); Constipation 0.7 (0.7). PCoA illustrated significant differences in the microbial communities in SSc versus healthy controls in both the cecum (R2=0.9, p=0.001) and sigmoid (R2=0.9, p=0.002) (Figure 1 ). Pairwise comparisons between SSc and healthy samples demonstrated numerous significant differences in bacterial genera of the cecum and sigmoid. Similar to chronic inflammatory states, such as inflammatory bowel disease (IBD), SSc patients had decreased commensal genera, such as Bacteroides and Faecalibacterium, and increased pathogenic genera, such as Enterobacteriales and Fusobacterium, compared with healthy controls in the cecum and sigmoid. However, SSc patients had increased sigmoid and cecum Bifidobacterium, which is typically found in lower abundance in IBD. Additional taxa alterations were observed, and the relationship between the microbial consortium and GIT symptoms was also explored and will be presented. Conclusions: This study demonstrates a distinct microbial signature in the colon of SSc patients compared with healthy controls. This unique ecological change may perpetuate immunological aberrations and contribute to clinical manifestations of SSc. Disclosure of Interest: None declared